2008
DOI: 10.1093/mutage/gen014
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological applications and significance of the comet assay

Abstract: Application of the single-cell gel electrophoresis or comet assay has revolutionized the field of genetic ecotoxicology or eco-genotoxicology. It is a rapid, sensitive and relatively inexpensive method providing the opportunity to study DNA damage (including oxidative damage), repair and cell death (apoptosis) in different cell types without prior knowledge of karyotype and cell turnover rate. The assay has, however, often attracted criticism for its lack of ecotoxicological relevance. In addition, in contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
247
0
23

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(272 citation statements)
references
References 158 publications
2
247
0
23
Order By: Relevance
“…Some studies have previously reported on the genotoxic and mutagenic potential of organophosphate insecticide cholrprifos and monocorotofos in C.punctatus (Ali et al, 2008). It is well established that toxicants with oxidative stress have the potential to attack DNA resulting in clastogenic and molecular damages (Jha, 2008). An increase in the frequency of MN in dimethoate treated fish is an indication of chromosome damage.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have previously reported on the genotoxic and mutagenic potential of organophosphate insecticide cholrprifos and monocorotofos in C.punctatus (Ali et al, 2008). It is well established that toxicants with oxidative stress have the potential to attack DNA resulting in clastogenic and molecular damages (Jha, 2008). An increase in the frequency of MN in dimethoate treated fish is an indication of chromosome damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to limited antioxidant protection and quite high unsaturated fatty acid content, fish sperm has been shown sensitive to oxidative stress involved in DNA damage after exposure to physical or chemical stresses (Li and Reinberg 2011;Cabrita et al 2011;Hulak et al 2013;Labbe et al 1995;. Such characteristics make spermatozoa a relevant and sensitive target to assess reproductive impairment through the loss of DNA integrity as demonstrated in several aquatic organisms exposed to environmental stressors (Galloway et al 2010;Jha AN 2008;Lacaze et al 2011;Santos et al 2013a). …”
Section: Environmental Factorsmentioning
confidence: 99%
“…The preview of the comets was processed using the program CometScore TM (version 1.5, TriTek Corp., Sumerduck, VA). The DNA DSB were assessed by the most informative and precise parameter OTM (Olive tail moment, the distance from the center of the head to the density center of the comets tail multiplied by tDNK[%]) (Olive 1999;Jha 2008). For each variant of each replicate 100 cells were counted (in total 300 cells per one variant were analyzed).…”
Section: Dna Damage Analysismentioning
confidence: 99%